SCHOOL PRINCIPAL'S ADMINISTRATIVE LEADERSHIP IN ENHANCING SCHOOL MANAGEMENT EFFECTIVENESS: CHALLENGES AND STRATEGIES IN THE DIGITALEDUCATION ERA - Ichwanudin Ichwanudin; Mega Safita Putri; Bq Risqi Irhamni (Program Studi Manajemen Pendidikan Islam, 2026)
This study aims to analyze the role of the school principal as an administrator in improving the effectiveness of school management, focusing on three main aspects: the principal’s administrative competencies in managing curriculum administration, human resources, finance, facilities and infrastructure, and student affairs; strategies for implementing effective educational management; and the challenges faced. This study employs a qualitative approach using a case study design conducted at MTs Darul Fikri. Data collection was carried out through semi-structured in-depth interviews with the school principal, teachers, administrative staff, and the school committee; moderate participant observation over three days; and document analysis. Data analysis utilized the Miles and Huberman interactive model, which includes the stages of data reduction, data presentation, and drawing conclusions, with data validity ensured through triangulation of sources, methods, and time. The research results indicate that school principals play a crucial role in managing all aspects of school administration—including curriculum, personnel, finance, facilities, and student affairs—in a systematic, participatory, and quality-improvement-oriented manner. Effective management implementation strategies include SWOT analysis-based strategic planning, collaborative organization, adaptive program implementation, and continuous formative evaluation. However, school principals face three major challenges: limited digital infrastructure, rapid changes in education regulations, and increasing demands for public accountability. This study concludes that the effectiveness of school management depends heavily on the principal’s capacity to perform administrative functions in an integrated, adaptive, and accountable manner, supported by adequate resources and a conducive regulatory system.